First-Order Certainty Equivalence with Instrument-Dependent Randomness - Laffont, Jean-Jacques (Review of Economic Studies, 1975)
Journal Article First-Order Certainty Equivalence with Instrument-Dependent Randomness Get access Jean-Jacques Laffont Jean-Jacques Laffont University of Montreal Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 4, October 1975, Pages 605–614, https://doi.org/10.2307/2296797 Published: 01 October 1975